Oral peptide therapeutics for diabetes treatment: State-of-the-art and future perspectives - Bingwen Ding; Zhu Zhu; Cong Guo; Jiaxin Li; Yong Gan; Miaorong Yu (Elsevier, 2024)
Diabetes, characterized by hyperglycemia, is a major cause of death and disability worldwide. Peptides, such as insulin and glucagon-like peptide-1 (GLP-1) analogs, have shown promise as treatments for diabetes due to their ability to mimic or enhance insulin's actions in the body. Compared to subcutaneous injection, oral administration of anti-diabetic peptides is a preferred approach. However, biological barriers significantly reduce the efficacy of oral peptide therapeutics. Recent advancements in drug delivery systems and formulation techniques have greatly improved the oral delivery of peptide therapeutics and their efficacy in treating diabetes. This review will highlight (1) the benefits of oral anti-diabetic peptide therapeutics; (2) the biological barriers for oral peptide delivery, including pH and enzyme degradation, intestinal mucosa barrier, and biodistribution barrier; (3) the delivery platforms to overcome these biological barriers. Additionally, the review will discuss the prospects in this field. The information provided in this review will serve as a valuable guide for future developments in oral anti-diabetic peptide therapeutics.